ANALISIS NORMATIF PERATURAN PARIWISATA NUSA TENGGARA BARAT DAN IMPLIKASINYA BAGI PENGEMBANGAN PARIWISATA PULAU LOMBOK - I Gede Angga Permana; Putu Arya Reksa Anggratyas (Institut Agama Hindu Negeri Gde Puda Mataram, 2026)
Tourism is a strategic sector for the economic development of West Nusa Tenggara Province and Lombok Island, requiring a comprehensive regulatory framework to ensure legal certainty and sustainable destination governance. This study aims to analyse the normative construction of Regional Regulation of West Nusa Tenggara Province Number 3 of 2025 on the Implementation of Tourism, examine its vertical harmonisation with Law Number 10 of 2009 on Tourism, and formulate its normative implications for tourism development on Lombok Island. This research employs a normative legal method (doctrinal legal research) with statutory, conceptual, and historical approaches. Primary legal materials consist of Regional Regulation NTB No. 3/2025, Law No. 10/2009, and related regulations, while secondary materials include journal articles and scientific publications on regional tourism policy. The analysis applies grammatical and systematic interpretation to assess consistency and hierarchical coherence. The findings indicate that Regional Regulation NTB No. 3/2025 has a comprehensive structure covering seven dimensions of tourism implementation and adopts the BGCAM pentahelix model to support collaborative governance. Vertically, the regulation aligns with Law No. 10/2009 in terms of principles of implementation, allocation of authority, and guarantees of community participation, and incorporates a risk-based business licensing paradigm consistent with the Job Creation Law. Its normative implications include opportunities to strengthen destination governance through collaborative organisations, integrate spatial control and carrying capacity, and reinforce local economic empowerment. However, effective implementation still requires operational implementing regulations, cross-sectoral coordination mechanisms, and the establishment of Destination Management Organizations at the destination level to ensure tangible benefits for the welfare of Lombok’s communities.